A comparison between a shakedown design approach and the analytical design approach in the UK for flexible road pavements - Wang, Juan; Liu, Shu; Yu, Hai-Sui (Elsevier, 2016)
Recently a shakedown approach has been proposed for structural design of flexible road pavements (Wang and Yu, 2013a). This new approach makes use of both elastic and plastic properties of materials, and therefore represents an advance from the existing analytical design approach in the UK where pavement life is related with elastic strains at critical locations using empirical equations. However, no direct comparison between designs using these two approaches has been made to date. In this paper, following a brief review of both approaches, the shakedown approach based on Wang and Yu (2013a) is used to design layer thicknesses for a typical asphalt pavement considered in the analytical approach TRRL Report LR1132. Typical values of plastic parameters are chosen for pavement materials at temperature 20°C, while stiffness moduli of materials are kept identical with the analytical design. The resulting shakedown designs are then compared with the thickness design chart using the analytical design approach. And the influence of temperature on the shakedown-based thickness design is also discussed in detail. It is found that if the shakedown design approach is conducted against the maximum wheel pressure at a relatively high temperature, the resulting pavement structure will probably not fail due to excessive rutting within the service life.